A Randomized Controlled Pilot Study of the Triple Stimulation Technique in the Assessment of Electroacupuncture for Motor Function Recovery in Patients with Acute Ischemic Stroke. (10th June 2013) - Tan, Feng; Wang, Xuewen; Li, Hui-qin; Lu, Lin; Li, Ming; Li, Ji-huang; Fang, Meifeng; Meng, Di; Zheng, Guo-qing
Abstract : The objective of this pilot study was to objectively assess electroacupuncture for motor function recovery in patients with acute ischemic stroke using the triple-stimulation technique (TST). The patients received either electroacupuncture plus western conventional medication (WCM) (n = 32 ) or single WCM (n = 31 ) for 14 days. The total clinical effective rate was statistically significantly superior in electroacupuncture group to that in WCM group (P < 0.01 ). Fugl-Meyer Assessment Scale (FMA) score, National Institutes of Health Stroke Scale (NIHSS) score, and T S T r a t i o were statistically more significant in electroacupuncture group than those in WCM group (P < 0.01 ). There was positive correlation between T S T r a t i o and NIHS score both before and after treatment (P < 0.01 ) and negative correlation between T S T r a t i o and FAM score both before treatment and after treatment (P < 0.01 ). Comparing between the two groups or between pretreatment and posttreatment, adverse events, electrocardiogram, liver function, and kidney function showed no statistically significant difference (P > 0.05 ). In conclusion, electroacupuncture was beneficial for the motor function recovery of patients with acute ischemic stroke and was generally safe. TST can be used for quantitative evaluation of electroacupuncture for motor function recovery in patients with acute ischemic stroke because it can objectively analyze the injury and recovery of corticospinal tract impairments.